Representasi Nilai Kepedulian Lingkungan dalam Buku Cerita Anak "Balapan Sampah" - Nur Hikma; Juanda Juanda; Usman Pahar; Hadryanti (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2026)
Children’s storybooks play an important role in instilling character and educational values. One essential value that should be introduced early is environmental awareness. This study aims to analyze the representation of environmental awareness values in the children’s storybook "Balapan Sampah" (Trash Race). The research employed a qualitative approach using content analysis of the story text. The data consisted of words, phrases, sentences, character dialogues, and events reflecting environmental awareness values. Data were analyzed through close reading, data reduction, categorization, and meaning interpretation based on Stuart Hall’s theory of representation. The findings show that the story represents several environmental awareness values, including maintaining environmental cleanliness, disposing of waste properly, managing waste responsibly, and cooperating to protect the environment. These values are conveyed implicitly through characters’ actions, dialogues, and plot events. The study concludes that "Balapan Sampah" has strong potential as a children’s literary learning medium for fostering environmental awareness and character development from an early age. Abstrak: Buku cerita anak memiliki peran penting dalam menanamkan nilai karakter dan edukatif. Salah satu nilai penting yang perlu diperkenalkan sejak dini ialah kepedulian lingkungan. Penelitian ini bertujuan menganalisis representasi nilai kepedulian lingkungan dalam buku cerita anak ”Balapan Sampah”. Penelitian menggunakan pendekatan kualitatif dengan metode analisis isi terhadap teks cerita. Data berupa kata, frasa, kalimat, dialog tokoh, dan peristiwa yang memuat nilai kepedulian lingkungan. Analisis dilakukan melalui pembacaan menyeluruh, reduksi data, pengelompokan, dan penafsiran makna dengan perspektif teori representasi Stuart Hall. Hasil penelitian menunjukkan bahwa cerita ini merepresentasikan nilai menjaga kebersihan lingkungan, membuang sampah pada tempatnya, mengelola sampah dengan baik, serta bekerja sama menjaga lingkungan. Nilai-nilai tersebut disampaikan secara implisit melalui tindakan tokoh, dialog, dan alur cerita. Buku ”Balapan Sampah” berpotensi menjadi media pembelajaran sastra anak untuk menanamkan kepedulian lingkungan dan membentuk karakter sejak dini pada anak